Method development for Lawsone estimation in Trichup herbal hair powder by high-performance thin layer chromatography - Maunang M Patel; Bhavna R Solanki; Nilesh C Gurav; Prateek H Patel; Shweta S Verma (Wolters Kluwer Medknow Publications, 2013)
A simple, specific, accurate, precise and robust high-performance thin-layer chromatographic method has been developed and validated for estimation of Lawsone in Trichup herbal hair powder (coded as a THHP), polyherbal formulation. The chromatographic development was carried out on aluminum plates pre-coated with silica gel 60F 254 and good resolution was achieved with Toluene: Ethyl acetate: Glacial acetic acid (8:1:1 v/v/v) as mobile phase. Lawsone detection was carried out densitometrically at 277 nm and obtained retardation factor value was 0.46 ± 0.02. The method was validated with respect to specificity, linearity, accuracy, precision and robustness. The calibration curve was achieved to be linear over a range of 5-60 μg/ml and regression coefficient was obtained 0.998. Accuracy of chromatographic method was evaluated by standard addition method; recovery was obtained 99.25 ± 0.61% . The peak purity of Lawsone was achieved 0.999 r. Relative standard deviation for intraday and inter-day precision was 0.37-0.56% and 0.42-0.55%, respectively. The limit of detection and limit of quantification of the Lawsone were found to be 1.08 μg/m land 3.28 μg/ml, respectively. This result shows that the method was well validated. In the present study, the Lawsone content was found 0.322 ± 0.014% in THHP. This study reveals that the proposed high performance thin layer chromatography method is accurate, fast and cost- effective for routine estimation of Lawsone in polyherbal formulation.